2017
DOI: 10.1016/j.msec.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymeric nano/microspheres for selective and reversible adsorption of coronaviruses

Abstract: A novel biopolymeric material in the form of nano/microspheres was developed which was capable of adsorbing coronaviruses. The biopolymer was obtained by crosslinking of chitosan (CHIT) with genipin, a nontoxic compound of plant origin, in inverted emulsion and reacting the chitosan nano/microspheres obtained (CHIT-NS/MS) with glycidyltrimethyl-ammonium chloride (GTMAC). As a result the nano/microspheres of N-(2-hydroxypropyl)-3-trimethyl chitosan (HTCC-NS/MS) were obtained. HTCC-NS/MS were studied as the adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 44 publications
0
79
0
Order By: Relevance
“…A thin layer of flash-frozen sample is scanned using low energy electrons to get a 2D image of the sampleResolution: 3.4 Å 3D reconstruction of the HCoV-NL63 spike glycoprotein trimmer Walls et al, 2016;Baker, 2018 Atomic force microscope (AFM) AFM works by scanning the sample surface with a cantilever probe to which a LASER is pointed to measure surface variationsWorking modes-tapping mode, contact mode, and noncontact modeResolution: up to 30 nm Study the surface ultrastructure of SARS-CoVObserve the changes in the cell membrane during the release of a virion particleStudy the absorption of SARS-CoV viral particles in biopolymeric vesiclesTo study the structure and size of spike proteins which is present in the viral coat Yang, 2004;Lin et al, 2005;Eaton & West, 2010;Ng et al, 2004;Ciejka, Wolski, Nowakowska, Pyrc, & Szczubiałka, 2017;Lee et al, 2004 Fluorescence Lichtman & Conchello, 2005;Wang et al, 2008;Lu, Liu, & Tam, 2008;Manopo et al, 2005;Yuan et al, 2006;Yuan et al, 2005;Knoops et al, 2008 novel coronavirus that was successfully isolated from patients with SARS and identified them using TEM. The oropharyngeal sample from the patient was inoculated into Vero E6 mammalian cell lines (Ksiazek et al, 2003).…”
Section: Electron Microscopy Visualization Of Sars-covsmentioning
confidence: 99%
See 3 more Smart Citations
“…A thin layer of flash-frozen sample is scanned using low energy electrons to get a 2D image of the sampleResolution: 3.4 Å 3D reconstruction of the HCoV-NL63 spike glycoprotein trimmer Walls et al, 2016;Baker, 2018 Atomic force microscope (AFM) AFM works by scanning the sample surface with a cantilever probe to which a LASER is pointed to measure surface variationsWorking modes-tapping mode, contact mode, and noncontact modeResolution: up to 30 nm Study the surface ultrastructure of SARS-CoVObserve the changes in the cell membrane during the release of a virion particleStudy the absorption of SARS-CoV viral particles in biopolymeric vesiclesTo study the structure and size of spike proteins which is present in the viral coat Yang, 2004;Lin et al, 2005;Eaton & West, 2010;Ng et al, 2004;Ciejka, Wolski, Nowakowska, Pyrc, & Szczubiałka, 2017;Lee et al, 2004 Fluorescence Lichtman & Conchello, 2005;Wang et al, 2008;Lu, Liu, & Tam, 2008;Manopo et al, 2005;Yuan et al, 2006;Yuan et al, 2005;Knoops et al, 2008 novel coronavirus that was successfully isolated from patients with SARS and identified them using TEM. The oropharyngeal sample from the patient was inoculated into Vero E6 mammalian cell lines (Ksiazek et al, 2003).…”
Section: Electron Microscopy Visualization Of Sars-covsmentioning
confidence: 99%
“…After the initial adsorption quantified using reverse transcriptase‐quantitative polymerase chain reaction (RT‐qPCR), AFM was used to confirm that the virus particles were successfully attached to the biopolymer. AFM images revealed densely distributed particles approximately 140 nm (diameter) on the surface which were absent in the case of untreated vesicles (Ciejka et al, 2017).…”
Section: Visualization Of Sars‐covs By Atomic Force Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Several new approaches based on nanostructured materials have recently been established. Studies have reported the use of gold and silver nanoparticles, magnetic nanoparticles, carbon and polymeric nanostructured materials (Cao et al 2002, Theek et al 2014, Ye et al 2015, de Souza et al 2016, Ciejka et al 2017. Gold nanoparticles are particularly exciting and commonly described to be appropriated for many applications.…”
Section: Nanostructured Materials For Biosensor Fabricationmentioning
confidence: 99%